HUBUNGAN PENGETAHUAN DAN PERILAKU BERGANTIAN HANDUK, PAKAIAN ATAU ALAT SHALAT, TIDUR BERHIMPITAN DENGAN KEJADIAN SKABIES PADA SANTRI DI PONDOK PESANTREN AL-KAUTSAR BATAM - Rusdani, Rusdani; Susanti, Rini (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
Background scabies is a disease caused by ectoparasit Sarcoptes scabiei, which is mostly being ignored so that become a common health problems throughout the world. Scabies disease commonly affects individuals living in groups such as inhostels, boarding school, prisons, hospitals, densely populated settlements, and nursing homes that are equally at high risk for dissemination various skin diseases. The purpose of this research is to know the correlation between knowledge and the behavior of swapping towels, clothes or prayer tools, and crowded sleeping with the incident of scabies on students at Boarding School Al-Kautsar Batam. Method this research used the cross sectional methodology, with total sampling technique. As many as 122 students were taken for sample. Data were analyzed using chi-square. The results of this study indicate that there is a correlation between knowledge (p = 0,007, RR 3,026), swapping towels (p = 0,019, RR 2,614), alternately clothing or prayer tools (p = 0,006, RR 3,985), crowded sleeping (p = 0,001, RR 4,303) with the incident of scabies at Boarding School Al-Kautsar Batam. Conclusion Based on this research, it can be concluded that there is a significant correlation between knowledge and the behavior of swapping towels, clothes or prayer tools, crowded sleeping with the incident of scabies.